Maritime archaeological study on bronze gongs and ornaments from Tanjung Simpang Mengayau wreck salvage (2003) : Metal composition analysis - Masyella Masbaka (2014)
This thesis presents a quantitative result from the elemental Inductively Coupled Plasma – Optical Emission Spectrometry (hereafter known as ICP-OES) analysis for three bronze gongs and 10 copper alloy artifacts from the shipwreck site off the northernmost tip of Borneo, Tanjung Simpang Mengayau Wreck. Despite various tools and techniques to obtain the elemental composition of metal artifacts, ICPOES is considered modern and reliable analytical chemical instrument for these bronze artifacts from shipwreck and museum collection. The analyzed artifacts from the cargo, based on the decoration of ceramics pottery, patinas and colors evidence, are dated back to the Song Dynasty era circa 960 AD - 1279 AD. The elemental data would pertain the metal present in China and reflects the maritime trade by the Chinese to the Southeast Asian countries during the time period. These artifacts were analyzed using ICP-OES before a simple statistical data used to pick up the trend of their metal composition. Other studies have also been done on musical instruments were the type of gongs, preliminary study on the gongmaking in Borneo and briefly on its actual metal composition to today’s appearance. The analysis on recent gongs is dealing with its tune as percussive musical instruments. To the bronze ornaments, they are severely damaged due to the reaction of bronze metals to the sea-water in such a long period and being the only type of bronze found in the wreck site along with gongs. In par, the bronze ornaments are referred bronze mirror or bronze ornaments or bronze discs. The average of metal composition for bronze gongs is Cu 67.9%, Pb 3.7%, Sn 0.10%, As 0.080%, Fe 0.10%,Ag 0.052%, Ni 0.02%, Zn 0.010%, Mg 0.0015%, Au 0.0024%; meanwhile for the bronze ornaments is Cu 70.5%, Sn 0.070%, Zn 0.0063%, Pb 2.0%, Au 0.0024%, As 0.087%, Ag 0.040%, Ni 0.022%, Mg 0.014%, and Fe 0.0063%. The trend of metal compositions on bronze gongs implicitly shows no trending at all, but appears consistent in bronze ornament mostly in copper (89%), lead (10%), and tin (1%). Analytically, the contents shows the quality of these bronze artifacts to be used as currency apart from as trade goods. Regarding to the lack of elemental analysis on both artifacts from other sites in Southeast Asia, it cause difficulty to compare their composition for crossreferencing and for further provenance assessment.